Building robust supply chains by reducing vulnerability and improving resilience. (1st January 2012) - Vlachos, Dimitrios; Iakovou, Eleftherios; Papapanagiotou, Konstantinos; Partsch, Daniel
Powerful socioeconomic factors have been transforming dramatically supply chain networks, boosting the pursuit for resilience against disruptions, conflicts of interests and economic policies. As companies have to deal with disruptions that their outcome can have significant financial ramifications, both the academic world and industry keep now security and uninterrupted product flow from suppliers to end-users under close scrutiny. In this work, we study one of the dimensions of sustainable supply chains, that of supply chain risk management. To this end we provide definitions, methods, procedures, regulatory interventions aiming in reducing vulnerability and improving resilience as well as related business cases.